Acetylcholine release in mouse hippocampal CA1 preferentially activates inhibitory-selective interneurons via α4β2* nicotinic receptor activation - Bell, L. Andrew; Bell, Karen A.; McQuiston, A. Rory (Frontiers in Cellular Neuroscience, 2015)
Acetylcholine (ACh) release onto nicotinic receptors directly activates subsets of inhibitory interneurons in hippocampal CA1. However, the specific interneurons activated and their effect on the hippocampal network is not completely understood. Therefore, we investigated subsets of hippocampal CA1 interneurons that respond to ACh release through the activation of nicotinic receptors and the potential downstream effects this may have on hippocampal CA1 network function. ACh was optogenetically released in mouse hippocampal slices by expressing the excitatory optogenetic protein oChIEF-tdTomato in medial septum/diagonal band of Broca cholinergic neurons using Cre recombinase-dependent adeno-associated viral mediated transfection. The actions of optogenetically released ACh were assessed on both pyramidal neurons and different interneuron subtypes via whole cell patch clamp methods. Vasoactive intestinal peptide (VIP)-expressing interneurons that selectively innervate other interneurons (VIP/IS) were excited by ACh through the activation of nicotinic receptors containing alpah4 and beta2 subunits (alpha4 beta2*). ACh release onto VIP/IS was presynaptically inhibited by M2 muscarinic autoreceptors. ACh release produced spontaneous inhibitory postsynaptic current (sIPSC) barrages blocked by dihydro-beta-erythroidine in interneurons but not pyramidal neurons. Optogenetic suppression of VIP interneurons did not inhibit these sIPSC barrages suggesting other interneuron-selective interneurons were also excited by 42* nicotinic receptor activation. In contrast, interneurons that innervate pyramidal neuron perisomatic regions were not activated by ACh release onto nicotinic receptors. Therefore, we propose ACh release in CA1 facilitates disinhibition through activation of 42* nicotinic receptors on interneuron-selective interneurons whereas interneurons that innervate pyramidal neurons are less affected by nicotinic receptor activation.